Особенности экстра- и интраорганной иннервации капсулы запястья некоторых млекопитающих, обусловленные типом опоры и скоростью передвижения - Ильенко, Н.Н. (Вестник зоологии, 1971)
Innervation of carpus capsule was studied by anatomical and histological methods. In some animals the capsule is innervated by ulnar and radial nerves, in other — by ulnar and median ones and by the branches of periosteum, muscle and vessel nerves. Three types of receptor are found: free, non-free non-incapculated and non-free incapsulated ones. The receptor types are njost variable in a horse (unguligrading) possessing the most perfect type of support and different speed of movement. The structure of incapsulated receptors is the most complex in a bear (plantigrading), which is connected with variation of its hand movements.